1987
DOI: 10.1111/j.1558-5646.1987.tb05804.x
|View full text |Cite
|
Sign up to set email alerts
|

LIMITED DISPERSAL AND PROXIMITY‐DEPENDENT MATING SUCCESS IN THE COLONIAL ASCIDIAN BOTRYLLUS SCHLOSSERI

Abstract: Abstract. -Although the propagules of many sessile organisms have the capacity to disperse over large distances, dispersal is often spatially restricted. In this paper, I document, using a combination of mark/recapture techniques and histocompatibility assays, dispersal distance of the planktonic larvae of the sessile, colonial sea squirt Botryllus schlosseri. Both of these methods indicate that most larvae remain within a meter of their birthplace. Such limited dispersal should lead to increased matings among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(16 citation statements)
references
References 80 publications
0
15
1
Order By: Relevance
“…Distances traveled by sperm of a colonial stolidobranch ascidian can exceed distances traveled by larvae (Grosberg, 1987(Grosberg, , 1991Yund, Murdock, & Johnson, 2007).…”
Section: Advantages Of Broodingmentioning
confidence: 99%
“…Distances traveled by sperm of a colonial stolidobranch ascidian can exceed distances traveled by larvae (Grosberg, 1987(Grosberg, , 1991Yund, Murdock, & Johnson, 2007).…”
Section: Advantages Of Broodingmentioning
confidence: 99%
“…The importance of G͞SCP as a selective factor may be quite dramatic in some populations. The rate of chimerism within natural populations of B. schlosseri can reach levels as high as 20% (9,26) and our data suggest a 40% incidence of G͞SCP within those chimeras. Finally, as predicted by Buss's hypothesis (1), we showed that the rate of G͞SCP drops considerably when colony rejection occurs instead of fusion.…”
Section: Discussionmentioning
confidence: 51%
“…In marine species that reproduce by broadcast spawning (i.e., shedding of male and female gametes into the water column) and that rely on water currents and movement of sperm between individuals, the rapid dilution and relatively short lifespan of sperm means that outcrossed fertilization is proximity- dependent [31]. In sessile organisms in which the only proximate partner is a clone- mate, self-fertilization becomes the only method of achieving meiotically-driven genetic variability.…”
Section: Discussionmentioning
confidence: 99%